Noninvasive evaluation of cerebrospinal fluid pressure in ocular hypertension: a preliminary study. Issue 5 (24th March 2018) - Xie, Xiaobin; Chen, Weiwei; Li, Zhen; Thomas, Ravi; Li, Yong; Xian, Junfang; Yang, Diya; Wang, Huaizhou; Zhang, Shoukang; Kang, Zefeng; Wang, Ningli; ,
Abstract: Purpose: To compare the orbital cerebral spinal fluid pressure (CSFP) and trans‐lamina cribrosa pressure difference (TLCPD) determined noninvasively in ocular hypertensive (OH) subjects and controls. Methods: Cross‐sectional observational study. Magnetic resonance imaging was used to measure orbital subarachnoid space width (OSASW). The CSFP (mm Hg) was estimated from a published formula as 17.54 × MRI derived OSASW at 15 mm behind the globe + 0.47 × body mass index + 0.13 × mean arterial blood pressure −21.52. Estimated TLCPD was calculated as IOP‐ CSFP. Results: The orbital subarachnoid space width was significantly wider (p   =   0.01) in the OH group than in the control group at all three measurement locations. The MRI derived CSFP value in OH (14.9 ± 2.9 mm Hg) was significantly higher than in the normal group (12.0 ± 2.8 mm Hg; p   <   0.01). The estimated TLCPD value in OH (9.0 ± 4.2 mm Hg) was significantly higher than in controls (3.6 ± 3.0 mm Hg; p   <   0.01). Conclusion: The wider OSASW and higher estimated CSFP in OH subjects suggest a higher orbital CSFP. Despite a higher orbital CSFP that could be protective, the higher TLCPD in OH may play a significant role in the risk of developing glaucoma.